ANALISIS MANFAAT VIDEO TUTORIAL PPKn (POKOK BAHASAN PENGARUH KEMAJUAN IPTEK TERHADAP NKRI) SISWA KELAS XII SMKN PERTANIAN TERPADU PROVINSI RIAU - Deswita Natalia Pakpahan; Sri Erlinda; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was conducted to determine the benefits of PPKn video tutorials (the topic the effect of advancements in science and technology on the Republic of Indonesia), particularly in supporting online learning activities during the current coronavirus pandemic. The wording of the problem in this study this how PPKn benefits video tutorias (the topic in the influence of scientific and technological progress on the Republic of Indonesia) from class XII students of SMKN Pertanian Terpadu Riau Province. This Study aims to determine the benefits of PPKn video tutorials (the topic of the influence of scientific and technological progress on NKRI) in class XII student of SMKN Pertanian Terpadu Riau Province.The advantage of this research is that it can be used as a reference source for schools and subject teachers, in particular by enhancing creativityin the teaching throgh video tutorials. In this study, the writer will present the data resulting from the research conducted by the writer at the research site, which is being conducted at SMKN Pertanian Terpadu, Riau province on Jl. Kaharudin Nasution, KM. 10 Marpoyan Damai Subdistrict Maharatu Village RT/RW 03/02 poscode 282824. This study was conducted in September-December 2020. This study used techniques for collecting interview data, questionnaires and documentation. In this study, the population was 456 students, so the authors took a sample of 20% of the total population. Thus, the number of samples in this study was 91 students as respondents who completed the author's research questionnaire using the Proportional Random Sampling technique using the Suharsimi Arikunto formula. The results of this research have been analyzed using quantitative descriptive analysis techniques that aim to gain an overview of the respondents' answers to the research variables used. Based on the results of the study, the results of the mean presentation value of the alternative answers for the dominant respondents were determined to be 79.89%, with range ii being in the category 'Very useful' with presence in the range from 50.01-75%. Therefore, the analysis of the benefits of the PPKn instructional video (the topic of the influence of scientific and technological progress on the Republic of Indonesia) of class XII students of Riau Province Integrated Agriculture Vocational High School is very helpful.Key Words: Video Tutorial